Military Pilgrimage and Battlefield Tourism - Eade, John, author.
1 online resource
Keywords: "Military Pilgrimage and Battlefield Tourism is the first volume to bring together a detailed analysis of professional military pilgrimage with other forms of commemorating military conflict. The volume looks beyond the discussion of battlefield tourism undertaken primarily by civilians which has dominated research until now through an analysis of the relationship between religious, military and civilian participants. Drawing on a comparative approach towards what has mostly been categorised as secular pilgrimage, dark tourism/thanatourism, military and religious tourism, and re-enactment, the contributors explore the varied ways in which memory, material culture and rituals are performed at particular places. The volume also engages with the debate about the extent to which western definitions of pilgrimage and tourism, as well as such related terms as religion, sacred and secular, can be applied in non-western contexts. "--Provided by publisher.